Sodium-ion battery negative electrode material and preparation method and application thereof
By preparing FeP@C nanocomposite structure, the problem of volume expansion and poor conductivity of sodium ion battery materials is solved, and excellent cycling and rate performance are achieved.
Patent Information
- Application Number
- CN202411379005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing sodium ion battery materials have problems such as insufficient capacity, insufficient cycle life, low energy density, low ion conductivity, and unstable electrolyte.
By preparing a uniform FeP@C nanocomposite structure, phosphating is performed using Prussian blue material, and uniformly coated by graphene, a double-layer carbon-covered FeP composite material is formed to solve the problems of volume expansion and poor conductivity.
The excellent cycle performance and rate performance of the negative electrode material of sodium ion battery are achieved, which alleviates volume expansion, ensures the integrity of the electrode structure, and improves the conductivity.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials and electrochemistry, and specifically relates to a negative electrode material for a sodium ion battery and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in consumer electronics, energy storage power stations, electric vehicles and other fields. Compared with traditional lead-acid batteries, nickel-metal hydride batteries and other energy storage batteries, lithium-ion batteries have higher operating voltage, higher mass specific energy and volume specific energy. In addition, lithium-ion batteries also have the advantages of low pollution, high safety, long cycle life and no memory effect. However, the global reserves of lithium resources are very limited, which greatly limits the large-scale application of lithium batteries in the future. Because of this, it is urgent to develop the next generation of high-performance energy storage power sources that can replace lithium-ion batteries. Sodium, as an active metal element in the same main group as lithium, has extremely similar physical and chemical properties to lithium, and sodium is abundant in the earth's crust, so the price of sodium-ion battery raw materials is much lower than that of lithium battery raw materials. In summary, it is very feasible to develop high-performance sodium-ion batteries to replace lithium-ion batteries. Although sodium-ion batteries have potential application value, there are relatively few studies on sodium-ion batteries at present, and the radius of sodium ions is larger than that of lithium ions, which makes sodium-ion batteries have certain limitations in material selection.
[0003] The current problems faced by sodium-ion batteries are that the capacity of existing materials is not outstanding enough, the cycle life is not long enough, the energy density is low, the ion conductivity is low, and the electrolyte is unstable. We will design and develop negative electrode materials suitable for sodium-ion batteries based on nanotechnology and lithium-ion battery technology. The single substance P has a small atomic weight and a strong sodium ion embedding ability. It can generate Na3P with the single substance Na, and the theoretical specific capacity reaches 2596 mAh•g -1 , has the highest capacity among the current sodium-embedded materials, and compared with graphite, it has a safer working voltage, so it is a very promising negative electrode material for sodium-ion batteries. Among the various allotropes of elemental phosphorus, red P has been studied the most, but red phosphorus is an electronic insulator and does not have electrochemical activity. For this reason, metal phosphides have been widely studied, mainly because metal phosphides (FeP, CoP, Cu3P, NiP2) have a higher theoretical specific capacity on the one hand; on the other hand, compared with red phosphorus, metal phosphides produce inactive metal elements during the cycle process, so they have higher conductivity, smaller volume change, and simpler synthesis. However, when metal phosphides are used as negative electrode materials for sodium-ion batteries, they still have a relatively high volume expansion, which leads to problems such as material pulverization and shedding from the current collector surface during the cycle.
[0004] In order to solve the problems of metal phosphides, scientists have proposed many solutions, including reducing the size of metal phosphides to nanoscale, forming composite materials of metal phosphides with conductive carbon materials, etc. Iron phosphide has similar structure and electrochemical sodium storage performance to other phosphides, but because Fe is not only safe and pollution-free, but also abundant in reserves and low in price, FeP has a very attractive application prospect. At present, there are two main methods to improve the electrochemical performance of iron phosphide: 1) Nanoparticles: According to Fick's first law, nanoparticle FeP can shorten the transmission path of sodium ions, increase the specific surface area of electrode materials, increase the contact area between electrolyte and electrode sheets, reduce the charge transfer resistance, and thus increase the diffusion coefficient of sodium ions. 2) Carbon coating: Carbon coating can be achieved by in-situ polymer pyrolysis and other methods, or by adding additional carbon sources such as carbon nanotubes, graphene, etc. Summary of the invention
[0005] The present invention prepares a uniform FeP@C nanocomposite structure by preparing a Prussian blue material and further phosphating it. The FeP particles in the structure are nanometer-sized, and each particle is coated with a carbon layer, thereby solving the problem of volume expansion during the cycle; and the conductivity of the material is improved by uniformly coating with graphene to solve the problem of poor conductivity of the material. The method for preparing the negative electrode material of a sodium ion battery provided by the present invention comprises the following steps: Step 1: Use potassium ferrocyanide, polyvinyl pyrrolidone (PVP), and ferric chloride as raw materials for reaction, adjust the acidity with hydrochloric acid, and prepare Prussian blue cubes; Step 2: The prepared Prussian blue cubes are dispersed in water by adding cetyltrimethylammonium bromide (CTAB) to obtain a Prussian blue cube dispersion; and the graphene oxide dispersion is added thereto, stirred, ultrasonicated, and then subjected to a hydrothermal reaction to obtain a PB / RGO composite material; Step 3: Place the prepared PB / RGO composite material and sodium hypophosphite at both ends of a porcelain boat respectively, place the porcelain boat in a tubular furnace, and perform high-temperature sintering under a protective atmosphere to obtain a FeP@C / RGO composite material; wherein the sodium hypophosphite is placed at the front end of the airflow of the protective atmosphere.
[0006] The present invention combines the nano-sizing of FeP and the surface carbon coating to prepare a double-layer carbon-coated (graphene and pyrolytic carbon) FeP composite material (FeP@C / RGO). The double-layer carbon-coated nanocomposite material not only reduces the size of FeP to the nanoscale to reduce the local volume expansion, but also uniformly coats a layer of amorphous carbon on the surface of FeP nanoparticles when Prussian blue is phosphated to FeP. This uniform layer of amorphous carbon not only improves the conductivity of FeP nanoparticles, but also ensures that the morphology of FeP remains unchanged during the cycle through coating, thereby preventing FeP from falling off the current collector. In addition, the graphene coating introduced during the hydrothermal process can further alleviate the volume expansion of the composite material, and the three-dimensionally connected graphene can ensure the integrity of the material and improve the conductivity of the electrode. Through the synergistic effect of double-layer carbon coating and nano-sizing, not only the volume expansion of FeP is alleviated, ensuring the integrity of the electrode structure during the cycle, but also the conductivity of the electrode is improved, and the contact area between the electrolyte and the electrode is increased, so that it is expected that a sodium ion battery negative electrode material with excellent cycle performance and rate performance can be obtained.
[0007] In the first step of the above method, the molecular weight of the polyvinyl pyrrolidone (PVP) is between 35,000 and 40,000.
[0008] In the first step of the above method, the potassium ferrocyanide is analytically pure with a purity of 99%.
[0009] In the first step of the above method, the ferric chloride is analytically pure with a purity of 99%.
[0010] In the first step of the above method, the molar ratio of potassium ferrocyanide, polyvinyl pyrrolidone (PVP) and ferric chloride is 1:1:1. The pH value of the solution is adjusted to 1-3 with hydrochloric acid.
[0011] In the first step of the above method, the concentration of the hydrochloric acid is 1-4 mol / L.
[0012] In the first step of the above method, the reaction temperature is 75-85°C and the reaction time is 10-30h.
[0013] In the first step of the above method, after the reaction is completed, a centrifugal washing step is also included; the centrifugal speed can be 600-1200r / min.
[0014] In the second step of the above method, the purity of cetyltrimethylammonium bromide (CTAB) is 99%.
[0015] In the second step of the above method, the dosage ratio of the Prussian blue cube, hexadecyltrimethylammonium bromide and water is 1g: 0.1-0.15g: 10-20ml.
[0016] In the second step of the above method, the concentration of the graphene oxide dispersion is 3-5 mg / ml.
[0017] In the second step of the above method, the dosage ratio of the Prussian blue cubic dispersion and the graphene oxide dispersion is 1 ml: 5-15 ml.
[0018] In the second step of the above method, the stirring speed is 100-300 r / min, and the stirring time is 30-60 min.
[0019] In the second step of the above method, the ultrasonic time is 8-10 minutes.
[0020] In the second step of the above method, the temperature of the hydrothermal reaction is 160-200° C. and the time is 10-30 hours.
[0021] In the second step of the above method, the hydrothermal reaction can be carried out in an oven.
[0022] In the third step of the above method, the mass ratio of the PB / RGO composite material to sodium hypophosphite is 1:9-12.
[0023] In the third step of the above method, the protective atmosphere is argon (Ar).
[0024] In the third step of the above method, the sintering temperature is 300-500° C. and the sintering time is 3-5 hours.
[0025] The sodium ion battery negative electrode material (i.e., FeP@C / RGO composite material) prepared by the above method also falls within the protection scope of the present invention.
[0026] The present invention also protects a negative electrode material.
[0027] The negative electrode material includes the above-mentioned sodium ion battery negative electrode material (i.e., FeP@C / RGO composite material).
[0028] The present invention also protects a sodium ion battery.
[0029] The sodium ion battery comprises a negative electrode, and the material of the negative electrode comprises the negative electrode material containing the above-mentioned FeP@C / RGO composite material.
[0030] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares a uniform FeP@C nanocomposite structure by preparing a Prussian blue material and further phosphating the material. The FeP particles in the structure are nanometer-sized and each particle is coated with a carbon layer, thereby solving the problem of volume expansion during the cycle. The conductivity of the material is improved by uniformly coating the graphene to solve the problem of poor conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the preparation process of FeP@C / RGO composite materials; Figure 2 It is a comparison chart of cycle improvement of Examples 1, 2, 3 and a comparative sample. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0033] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0034] The molecular weight of polyvinylpyrrolidone (PVP) used in the following examples is 35,000-40,000.
[0035] Example 1: The preparation method of a high-performance negative electrode material for a sodium ion battery of the present invention comprises the following steps: In the first step, 10 g of potassium ferrocyanide, 3 g of PVP and 5 g of ferric chloride were added to 50 ml of water as raw materials, the pH of the solution was adjusted to 2 with hydrochloric acid (1 mol / L), reacted at 80°C for 24 h, centrifuged at 600 r / min for 30 min, and washed with deionized water to prepare Prussian blue cubes; In the second step, 1 g of the prepared Prussian blue cubes was weighed and uniformly dispersed in 15 ml of water by adding 0.1 g of CTAB, and 20 ml of 5 mg / ml graphene oxide dispersion was added thereto, stirred at 100 r / min for 40 min, ultrasonicated for 10 min, and then hydrothermally reacted in an oven at 180 ° C for 12 h to obtain a PB / RGO composite material; In the third step, the prepared PB / RGO composite material is washed and dried and 10 times the amount of sodium hypophosphite is placed at both ends of a porcelain boat respectively, and sintered in an argon atmosphere at 400°C in a tubular furnace for 5 hours to obtain a FeP@C / RGO composite material; the sodium hypophosphite is placed at the front end of the airflow.
[0036] Embodiment 2: The preparation method of a high-performance negative electrode material for a sodium ion battery of the present invention comprises the following implementation steps: In the first step, 10 g potassium ferrocyanide, 3 g PVP and 5 g ferric chloride were added to 50 ml water as raw materials, the pH was adjusted to 3 with hydrochloric acid (2 mol / L), reacted at 80°C for 24 h, centrifuged at 600 r / min for 30 min, and washed with deionized water to prepare Prussian blue cubes; In the second step, 1 g of the prepared Prussian blue cubes was weighed and uniformly dispersed in 15 ml of water by adding 0.1 g of CTAB, and 25 ml of 5 mg / ml graphene oxide dispersion was added, stirred at 100 r / min for 40 min, ultrasonicated for 10 min, and then hydrothermally reacted in an oven at 180 ° C for 24 h to obtain a PB / RGO composite material; In the third step, the prepared PB / RGO composite material is washed and dried and 10 times the amount of sodium hypophosphite is placed at both ends of a porcelain boat respectively, and sintered in an argon atmosphere at 400°C in a tubular furnace for 3 hours to obtain a FeP@C / RGO composite material; the sodium hypophosphite is placed at the front end of the airflow.
[0037] Embodiment 3: The preparation method of a high-performance negative electrode material for a sodium ion battery of the present invention comprises the following implementation steps: In the first step, 10 g potassium ferrocyanide, 3 g PVP and 5 g ferric chloride were added to 50 ml water as raw materials, the pH was adjusted to 2 with hydrochloric acid (4 mol / L), reacted at 80 ° C for 24 h, centrifuged at 600 r / min for 40 min, and washed with deionized water to prepare Prussian blue cubes; The second step is to weigh 1g of the prepared Prussian blue cubes and add 0.1g of CTAB to uniformly disperse them in 15ml of water, add 20ml of 5mg / ml graphene oxide dispersion, stir at 100r / min, ultrasonicate for 10min, and then hydrothermally react in an oven at 185°C for 12h to obtain a PB / RGO composite material; In the third step, the prepared PB / RGO composite material is washed and dried and 10 times the amount of sodium hypophosphite is placed at both ends of a porcelain boat respectively, and sintered in an argon atmosphere at 300°C in a tubular furnace for 5 hours to obtain a FeP@C / RGO composite material; the sodium hypophosphite is placed at the front end of the airflow.
[0038] Performance Test: The FeP@C / RGO composite materials prepared in Examples 1, 2, and 3 were used as negative electrodes and were enlarged. The active material (FeP@C / RGO composite material): conductive agent: binder were mixed, coated, and rolled according to a ratio of 92:8:8 to form a 2Ah small soft-pack battery. The cycle performance was compared at a voltage range of 2.0-3.95V at room temperature and a charge / discharge rate of 0.5C / 1C. The impedance of the electrode sheet after rolling was also compared. The comparison sample was the FeP uncoated state as the negative electrode, and the soft-pack was made using the same process. The test results are shown in Figure 2 and Table 1.
[0039] Cyclic performance: Examples 1, 2, and 3 all far exceed the comparative sample, among which Example 1 has the best cyclic performance; Electrical conductivity: Examples 1, 2, and 3 all far exceed the control sample, among which the electrode sheet of Example 1 has the lowest diaphragm resistance.
[0040] Table 1 is the comparison results of the film resistance of Examples 1, 2, 3 and the comparative sample
[0041] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, comprising the following steps: Step 1: Use potassium ferrocyanide, polyvinyl pyrrolidone and ferric chloride as raw materials to react, adjust the acidity with hydrochloric acid, and prepare Prussian blue cubes; Step 2: The prepared Prussian blue cubes are dispersed in water by adding hexadecyltrimethylammonium bromide to obtain a Prussian blue cube dispersion; and a graphene oxide dispersion is added thereto to perform a hydrothermal reaction to obtain a PB / RGO composite material; Step 3: Place the prepared PB / RGO composite material and sodium hypophosphite at both ends of the porcelain boat respectively, and place the porcelain boat in a tube furnace, and perform high-temperature sintering under a protective atmosphere to obtain the FeP@C / RGO composite material, which is the negative electrode material of the sodium ion battery; wherein, The sodium hypophosphite is placed at the front end of the air flow of the protective atmosphere.
2. The preparation method according to claim 1, characterized in that: In the first step, the molecular weight of the polyvinyl pyrrolidone is between 35,000 and 40,000.
3. The preparation method according to claim 1, characterized in that: In the first step, the molar ratio of potassium ferrocyanide, polyvinyl pyrrolidone and ferric chloride is 1:1:1 respectively; the pH value of the solution is adjusted to 1-3 with hydrochloric acid; and the concentration of the hydrochloric acid is 1-4 mol / L.
4. The preparation method according to claim 1, characterized in that: In the first step, the reaction temperature is 75-85° C. and the reaction time is 10-30 h.
5. The preparation method according to claim 1, characterized in that: In the second step, the dosage ratio of the Prussian blue cube, hexadecyltrimethylammonium bromide and water is 1g: 0.1-0.15g: 10-20ml; And / or, in the second step, the concentration of the graphene oxide dispersion is 3-5 mg / ml; And / or, the volume ratio of the Prussian blue cubic dispersion to the graphene oxide dispersion is 1:5-15.
6. The preparation method according to claim 1, characterized in that: In the second step, the temperature of the hydrothermal reaction is 160-200° C. and the time is 10-30 hours.
7. The preparation method according to claim 1, characterized in that: In the third step, the mass ratio of the PB / RGO composite material to sodium hypophosphite is 1:9-12; And / or, in the third step, the protective atmosphere is argon; And / or, in the third step, the sintering temperature is 300-500° C., and the sintering time is 3-5 hours.
8. A sodium ion battery negative electrode material prepared by the method according to any one of claims 1 to 7.
9. A negative electrode material, comprising the sodium ion battery negative electrode material according to claim 8. 10 . A sodium ion battery comprising a negative electrode, wherein the negative electrode comprises the negative electrode material according to claim 9 .
Citation Information
Patent Citations
Prussian blue / reduced graphene oxide composite material as well as preparation method and application thereof
CN104716314A
Graphene rapidly-coated Prussian blue sodium ion battery positive electrode material and preparation method thereof
CN108565422A
Graphene / carbon nanotube composite aerogel material modified by iron phosphide nanocubes, preparation method of composite aerogel material and lithium-sulfur battery
CN110745799A
Battery electrode and method of making the same
WO2024184371A1
Cited By
Negative plate and preparation method thereof
CN121641834A